Heat Inactivation of Coccidioides posadasii and Coccidioides immitis for Use in Lower Biosafety Containment. (September 2019) - Mead, Heather L.; Blackmon, Austin V.; Vogler, Amy J.; Barker, Bridget M.
Introduction: The difficulty involved in obtaining sufficient intact genomic deoxyribonucleic acid (DNA) from Coccidioides spp for downstream applications using published protocols prompted the exploration of inactivating mycelia and arthroconidia using heat under biosafety level 3 containment. This was followed by optimizing DNA extraction from mycelia using various methods at lower containment. Methods: Various exposure times and temperatures were examined to identify an effective heat inactivation procedure for arthroconidia and mycelia from both C immitis and C posadasii . Heat inactivation of mycelia was followed by DNA extraction using 2 commercially available kits, as well as a phenol:chloroform-based extraction procedure to determine DNA integrity and quantity among extraction methods using both live and heat-inactivated mycelia. Results: Ten-minute and 30-minute exposure times at 80°C were sufficient to inactivate Coccidioides spp arthroconidia and mycelia, respectively. DNA yield between live versus heat-inactivated mycelia was similar for each extraction procedure. However, DNA obtained using phenol:chloroform was of higher quantity and integrity compared with DNA obtained using the commercially available kits, which was highly fragmented. Conclusion: The ability to heat-inactivate Coccidioides cultures for processing at a lower level of containment greatly increased the efficiency of DNA extractions. Therefore, this is an ideal method for obtaining Coccidioides spp DNA and inactivated arthroconidia.